Yetişkin eğitimi çerçevesinde kentlileşme: Bursa örneği - Yıldız, Uğur (My University, 2008)
Bu araştırma, Bursa İlinde yaşayanların kentlilik düzeylerinin belirlenmesi amacıyla gerçekleştirilmiştir. Sağlıklı bir kentleşme kentlileşmeye olanak sağlarken bu olmadığı takdirde çarpık kentleşme olmaktadır. Bu durum kentlerde ciddi sıkıntılar oluşturmaktadır. Kentleşme kaynaklı sorunların çözümünde yetişkin eğitimi programları işlevsel çözümler sunmaktadır. Bu çalışmada araştırmacılar tarafından geliştirilen anket katılımcılara uygulanmıştır. Anket yedi bölümden oluşmaktadır. sel bilgiler”, ikinci bölüm, “Bursalılık ile ilgili bilgiler”, üçüncü bölüm “kentin tarihi ve doğal zenginliklerine katılım ile ilgili bilgiler”, dördüncü bölüm “kentin gündelik yaşam merkezlerine katılım ile ilgili bilgiler”, beşinci bölüm “yetişkin eğitimine katılım ile ilgili bilgiler”, altıncı bölüm “boş vakitleri değerlendirme şekilleri”, yedinci bölüm “kent ile ilgili bilgiler” şeklindedir. Araştırmanın örneklemini 2007- 2008 yıllarında Bursa Büyükşehir Belediyesinin yetişkinlere yönelik çeşitli etkinliklerine katılan 149 kişi (%67 kadın, %33 erkek) oluşturmaktadır. Bu örnekleme araştırmacılar tarafından geliştirilen anket uygulanmış ve şu bulgular elde edilmiştir. Yetişkinler beş ve daha uzun yıldır Bursa’da yaşamaktadırlar ve Bursa’da yaşamaktan memnundurlar. İyi bir Bursalı olmak için “kentlilik bilincinin” olması gerektiğini düşünmektedir. Kentin tarihi ve doğal zenginliklerine katılım yüksek oranlardadır. Örneğin Osmangazi ve Orhangazi Türbelerine gidenlerin oranı oldukça yüksektir. Kentin gündelik yaşam merkezlerine katılım oranı da yüksek seviyelerdedir. Büyük alışveriş merkezlerine, sinema, tiyatro ve konsere gidilmektedir. Yetişkin eğitimi etkinliklerine katılıma yönelik sorulara verilen cevaplarda Halk Eğitim Merkezleri’nin bilinirliği yüksek seviyede iken kurslarına katılım düşük kalmıştır. Sivil toplum kuruluşlarına üye olanların oranı da düşük seviyededir. Boş vakitlerin değerlendirilme şekillerin de TV izleme ilk sırada yer almıştır. Araştırmaya katılanların büyük kısmı kentlilik konusunda bilgili ve farkında iken uygulama ve katılımcılık noktasında daha düşük oranlarda kalmıştır. Çalışma bulgularına göre; Yerel yönetimlerin kentleşme sorunlarının aşılmasında kentlerinde yaşayanlara yetişkin eğitimi ilkelerine göre hazırlanan kentlilik bilinci eğitimleri düzenlemeleri önerilmektedir. Bu eğitimler kente karşı aidiyet duygusunun artmasını sağlayacak ve kentli davranışların öğrenilerek uygulanması sağlanacaktır. Kentlerin tarihi, doğal, kültürel, sanatsal ve gündelik yaşam merkezlerine katılımın artırılması için Hükümet, Yerel Yönetim ve Sivil Toplum Kuruluşlarının eşgüdümlü olarak etkinlikler düzenlemeleri önerilmektedir.

URBANIZATION ON THE FRAME OF ADULT EDUCATION: BURSA KEYS This research has been realized to determine the urbanization level of people who reside in the city of Bursa. A well-planned urbanization paves the way for becoming urbanized, but in the lack of it the result is irregular urbanization. This situation causes serious troubles in towns. The adult education programs provide functional solutions to the matters sourced from urbanization. In this study, the questionnaire which has been developed by the researchers has been applied to the participants. The questionnaire is formed from seven parts. In the first part there is individual information, in the second part there is information about being a Bursa citizen, in the third part there is knowledge about the participation of the citizens to the historical and natural riches of the city, in the fourth part there is information about the attendance to the daily life centers of the city, in the fifth part there is information about the participation about the adult education, in the sixth part there is information about the evaluation of the spare time, in the final part there is information about the city. The sample group of the research is formed of 149 people (67 % woman, 33% man) who participated in various activities of the Bursa Municipality for adults between years 2007 and 2008. The questionnaire which has been developed by the researchers has been applied to the sample group and the following results have been attained. The adults have been living in Bursa for five years or more than this and they are pleased to live in Bursa. They think that it is necessary to have the consciousness of citizenship to be a good citizen of the city of Bursa. The attendance to the natural and historical riches of the city is in high ratio. For instance, the proportion of the people who visit the Tombs of Osmangazi and Orhangazi is quite high. The participation of the people in daily life centers is also in high levels. People go to the hyper stores, cinema, theatre and concert. Considering the answers to the question about participation in activities on adult education, while the familiarity of the Public Education Centers is on a high level, the participation to the courses is on a low level. The ratio of people who are a member of the non-Governmental Society is also on a low level. Watching television has been selected in the first place in the participants’ evaluation of spare time. In the knowledge test, the municipal employee has got the highest grade. Many of the participants of the research are well-informed and are aware of urbanization but they are in low ratio in practicing and participation. According to this study results, it is advised to organize urbanization consciousness trainings prepared in harmony with the principles of adult education order to overcome the matter related with the urbanization by local administrations for the people who live in their towns. These trainings will increase the sense of state of belonging for the town and they will ensure the teaching and the application of the citizen behaviors. It is recommended to organize coordinated activities by the Government, Local Administration and Non-Governmental Organizations in order to raise the participation of the citizens to the historical, natural, cultural, artistic and daily life centers of the cities.
Keywords: Kentleşme_Bursa; Yetişkin Eğitimi